SOCIO-POLITIC PRE-CONDITIONS OF TERRORIST EXISTENCE IN THE EUROPE - Целуйко, М.Є. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2015)
The article reveal conditions, that conducive to appearance of radical mussulman part of inhabitants, appearance and existence the cell of terrorist organizations. On example of situation, that shaped in the Grate Britane, Gemany and France, common problems for the west European countries, that brought to terrorist action on this territories are showed.